Peran Sejarah Kebudayaan Islam dalam Membentuk Kesadaran Historis Generasi Muda - Afiyatun Kholifah; Abdul Goni; Enci Rahayu; Imam Alfarid (Pusat Riset dan Inovasi Nasional, 2026)
Technological developments and globalization have brought changes to the mindsets and behaviors of the younger generation, including a declining interest in history learning and low historical awareness. Islamic Cultural History (ISH) plays a crucial role in shaping historical awareness because it encompasses values ​​of faith, scholarship, tolerance, leadership, and morals relevant to modern life. This study aims to analyze the role of ISH learning in shaping the historical awareness of the younger generation, explain its importance in understanding Islamic historical values, and examine the effective implementation of ISH learning in the modern era. This study used a qualitative method with a library research approach. Data were obtained from books, scientific journals, articles, and various other sources relevant to the research theme. Data were analyzed descriptively and analytically through a process of collection, reduction, interpretation, and drawing conclusions. The results indicate that ISH learning plays a significant role in building the historical awareness of the younger generation by instilling Islamic character values ​​and identity. Historical awareness helps students understand the interconnectedness of the past, present, and future, enabling them to draw lessons from historical events. Implementation of Islamic Education (SKI) learning can be carried out through a contextual approach, active learning methods, the use of digital technology, role models, and experiential learning. Thus, SKI serves not only as a means of transferring knowledge but also as a medium for character and identity formation for the younger generation in the era of globalization.